2022
DOI: 10.1038/s41598-022-21909-7
|View full text |Cite
|
Sign up to set email alerts
|

λ-Carrageenan promotes plant growth in banana via enhancement of cellular metabolism, nutrient uptake, and cellular homeostasis

Abstract: Banana (Musa acuminata) is an important fruit crop and source of income for various countries, including Malaysia. To date, current agrochemical practice has become a disputable issue due to its detrimental effect on the environment. λ-carrageenan, a natural polysaccharide extracted from edible red seaweed, has been claimed to be a potential plant growth stimulator. Hence, the present study investigates the effects of λ-carrageenan on plant growth using Musa acuminata cv. Berangan (AAA). Vegetative growth such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 58 publications
2
2
0
Order By: Relevance
“…FTIR analysis is relevant in order to understand how the polysaccharide-based solutions affected the turnip greens at a metabolic and molecular level [57]. If we compare the FTIR-ATR similarity rate between the samples treated with polysaccharide solutions and the negative or positive controls, it corroborates all the previous results (biochemical characterization) with numbers.…”
Section: Discussionsupporting
confidence: 78%
“…FTIR analysis is relevant in order to understand how the polysaccharide-based solutions affected the turnip greens at a metabolic and molecular level [57]. If we compare the FTIR-ATR similarity rate between the samples treated with polysaccharide solutions and the negative or positive controls, it corroborates all the previous results (biochemical characterization) with numbers.…”
Section: Discussionsupporting
confidence: 78%
“…These ndings con rm those obtained in other studies treating other species with algae extracts(Banjare et al, 2022;Mutale-Joan et al, 2020;Rathore et al, 2009). Studies have indicated that the improved nutrient uptake by plants from seaweed extracts is attributed to the upregulation of genes involved in nutrient absorption(Billard et al, 2014), as well as an increase in chlorophyll, protein, and phenolic content due to the presence of microelements and plant growth regulators such as cytokinin(Thye et al, 2022;Zodape, 2001).…”
supporting
confidence: 86%
“…Lack of nutrients in a soil can result in leaf chlorosis, reduced plant development, and even plant death. However, the excess of nutrients in the soil can also have harmful effects on plants, affecting the plant nutrient uptake, resulting in oxidative stress, cell damage, and growth inhibition [60]. Plants require 16 essential elements to survive, such as carbon (C), hydrogen (H), oxygen (O), nitrogen (N), phosphorus (P), potassium (K), calcium (Ca), magnesium (Mg), sulfur (S); and trace elements, such as iron (Fe), zinc (Zn), manganese (Mn), copper (Cu), boron (B), molybdenum (Mo), and chlorine (Cl).…”
Section: Discussionmentioning
confidence: 99%